History of economic thought's place in macroeconomics revisited - David E. W. Laidler (The University of Western Ontario, Department of Economics, 2023)
The History of Economics Society was founded at a time when the History of Economic Thought was being expelled from the Economics post-graduate curriculum in many universities, and was one of the key institutions around which the sub-discipline successfully re-organised itself and continued to develop. Laidler (2003) argued that Economics itself, especially Macroeconomics, was suffering serious damage from this expulsion. It has continued to do so since.
Keywords: B2; B22; B41; E10; 330; History of Economic Thought; Macroeconomics; New Classical Economics; Empiricism; Deductivism